2011
DOI: 10.1152/ajpheart.00729.2011
|View full text |Cite
|
Sign up to set email alerts
|

A selective phosphodiesterase 3 inhibitor rescues low Po2-induced ATP release from erythrocytes of humans with type 2 diabetes: implication for vascular control

Abstract: Erythrocytes, via release of ATP in areas of low oxygen (O(2)) tension, are components of a regulatory system for the distribution of perfusion in skeletal muscle ensuring optimal O(2) delivery to meet tissue needs. In type 2 diabetes (DM2), there are defects in O(2) supply to muscle as well as a failure of erythrocytes to release ATP. The goal of this study was to ascertain if a phosphodiesterase 3 (PDE3) inhibitor, cilostazol, would rescue low O(2)-induced ATP release from DM2 erythrocytes and, thereby, enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
67
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(77 citation statements)
references
References 37 publications
10
67
0
Order By: Relevance
“…We openly acknowledge this limitation in our manuscript and are working to develop a selective antagonist. However, with respect to hypoxic vasodilation in resistance vessels, a number of important observations support our data: (1) perfusion of isolated resistance vessels with a buffer lacking erythrocytes fails to elicit vasodilation when extraluminal oxygen tension is reduced 11 ; (2) perfusion of isolated skeletal muscle resistance vessels with erythrocytes not capable of releasing ATP does not elicit vasodilation in response to this stimulus 12,13 ; (3) rescuing low O 2 -induced ATP release from diseased erythrocytes restores vasodilation when extraluminal oxygen tension is reduced. 12 These studies to date have not been performed within contracting muscle, and although this would be technically difficult, is certainly an area in need of future investigation.…”
Section: The Age-old Tale Of Skeletal Muscle Vasodilation: New Ideas supporting
confidence: 83%
See 1 more Smart Citation
“…We openly acknowledge this limitation in our manuscript and are working to develop a selective antagonist. However, with respect to hypoxic vasodilation in resistance vessels, a number of important observations support our data: (1) perfusion of isolated resistance vessels with a buffer lacking erythrocytes fails to elicit vasodilation when extraluminal oxygen tension is reduced 11 ; (2) perfusion of isolated skeletal muscle resistance vessels with erythrocytes not capable of releasing ATP does not elicit vasodilation in response to this stimulus 12,13 ; (3) rescuing low O 2 -induced ATP release from diseased erythrocytes restores vasodilation when extraluminal oxygen tension is reduced. 12 These studies to date have not been performed within contracting muscle, and although this would be technically difficult, is certainly an area in need of future investigation.…”
Section: The Age-old Tale Of Skeletal Muscle Vasodilation: New Ideas supporting
confidence: 83%
“…However, with respect to hypoxic vasodilation in resistance vessels, a number of important observations support our data: (1) perfusion of isolated resistance vessels with a buffer lacking erythrocytes fails to elicit vasodilation when extraluminal oxygen tension is reduced 11 ; (2) perfusion of isolated skeletal muscle resistance vessels with erythrocytes not capable of releasing ATP does not elicit vasodilation in response to this stimulus 12,13 ; (3) rescuing low O 2 -induced ATP release from diseased erythrocytes restores vasodilation when extraluminal oxygen tension is reduced. 12 These studies to date have not been performed within contracting muscle, and although this would be technically difficult, is certainly an area in need of future investigation. In line with the authors' suggestion, we, too, would support in vivo animal experimentation aimed at deciphering the critical role of red cells to vasodilation through use of pannexin-1 knockout, but it must be acknowledged that ATP release is not universal to a single channel, and impaired ATP release appears to depend on the specific signaling pathway.…”
Section: The Age-old Tale Of Skeletal Muscle Vasodilation: New Ideas supporting
confidence: 83%
“…Importantly, it has been reported that low O 2 -induced ATP release from erythrocytes of humans with type 2 diabetes is severely impaired (38,42,44). Moreover, these cells do not stimulate dilation of isolated, perfused skeletal muscle arterioles exposed to reduced extraluminal O 2 , a model of increased tissue O 2 Fig.…”
Section: Discussionmentioning
confidence: 91%
“…In support of this hypothesis, it was reported that isolated skeletal muscle arterioles perfused with erythrocytes from healthy humans-cells that respond to low O 2 with ATP release-dilate when exposed to reduced, extraluminal O 2 , a model of increased tissue O 2 need (11,43). In contrast, low O 2 -induced ATP release from erythrocytes from humans with type 2 diabetes is severely impaired (38,42,44), and these cells do not stimulate dilation of isolated, perfused skeletal muscle arterioles under similar conditions (42).…”
mentioning
confidence: 89%
See 1 more Smart Citation